Meðferð við sykursýki tegund 2 á Heilbrigðisstofnuninni Selfossi - Margrét Dís Óskarsdóttir; Ragnar Gunnarsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2007)
Hægt er að lesa greinina í heild sinni með því að smella á hlekkinn View/Open OBJECTIVE: Diabetes mellitus type 2 is a common and serious health problem (1). Long term complications reduce quality of life and even life expectancy as well as increasing greatly the cost of health care (1). Complications include macrovascular changes ,coronary heart disease and stroke and also microvascular changes such as ophthalmological, renal and neural damage. With effective control of blood glucose levels and blood pressure for instance, the probability of these complications can be diminished (2). Increased knowledge, new drugs and the publication of clinical guidelines raise the question whether this improves the level of care for diabetics in this rural Health-care Center. MATERIAL AND METHODS: This is a retrospective objective research spanning the years 1999-2003. Data was collected from the journals of 60 patients chosen randomly from the 130 patients diagnosed with diabetes mellitus type 2 during the same period of time. The available data from electrocardiograms, ophthalmologic-, foot and neural examinations, blood pressure measurements, body mass indexes and weight, were all recorded, along with the year of data collection. Also, all the blood tests research data mentioned in the Icelandic Diabetic type 2 Clinical Guidelines were recorded (4). RESULTS: The average age of persons in the sample was 69 +/- 11.5 years. Males were in a slight majority (59%) and the average weight was 96 +/- 21 kg amongst the 76% who were weighed during the period of investigation. The long term blood glucose mean value, HbA1c, dropped significantly from 7.46 +/- 1.2% at the onset of the period, to 6.53 +/- 0.7% at the termination of the period (p<0.01). Blood pressure dropped from 154 +/- 17,5 and 83 +/- 10,8 mmHg in the year 1999, to 138 +/- 18,1 and 80 +/- 8.4 mmHg during the year 2003 (p<0.01). In the year 1999 the total cholesterol was 5,7 +/- 0,7 mmol/l but in the year 2003 it was 4,7 +/- 0,9 mmol/l (p<0.01). The ...